PERANAN TIM PENGGERAK PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA DALAM UPAYA PERBAIKAN GIZI KELUARGA - Nasrah Natsir; Fatmawati Gaffar; Ahmad Syawaluddin (Universitas Negeri Makassar, 2020)
The purpose in this research are knowing the role of the coordinator of the familf welfare empowerment (PKK) in an effort to improve nutrition family in the village Kanjilo Kabupaten Gowa. This Study adopted qualitative approaches with the descriptive. Data collected by using observation, interview, and documentation. Data analyze by data collection, data reduction, data display and conclusion drawing/verifying. The role of the coordinator of the family welfare empowerment (PKK) in a effort to improve nutrition family in the village Kanjilo district Gowa, was implemented through the: Information about the importance of health services post nutritional supplements; monitoring of families that experienced the malnutrition; Concern the family against the clean and healthy living as well as food consumption pattern are all in good health and nutritional balanced; Reduction disorder due to lack of salt iodine (GAKY); Suplementasi the nutrient; The breastfeeding exclusive for 6 (six) months; Food a companion milk mother (MP-ASI).